Influence of surface active substances on the intensification of extraction when changing hydrodynamic indices of the technology of organopreparations - Paska, Maria; Drachuk, Uliana; Halukh, Bohdan; Basarab, Iryna (Eastern-European Journal of Enterprise Technologies, 2016)
An influence of surface-active substances (SAS) on the change of physical characteristics of extractants of the group of organic preparations (chonsorid, heparin, and ronidase) was studied. Authors established rational concentrations of SAS in extractants, at which the minimum of coefficient of surface tension and the decrease in coefficient of dynamic viscosity are reached. For the solution of extractant of chonsurid – SAS butanol in the concentration of 0,05–0,06 % by weight, of heparin – butanol in the concentration of 0,5–0,6 % by weight, of ronidase – butanol in the concentration of 0,45–0,6 % by weight. Mean values of a near–surface laminar layer were established with the help of theoretical calculations, namely: for heparin – 1 mm, for chonsurid – 3 mm, for ronidase – 1 mm. Kinetics of extracting demonstrated an increase in the amount of the mass of extract when using extractants with SAS: for chonsurid – by 1,4 times, for heparin – by 1,7 times, for ronidase – by 1,9 times. Mathematical calculations proved a change in the similarity numbers under the influence of the surfactants, the Archimedean, Euler and Reynolds numbers were calculated and their values were compared. The Archimedean number changes its value for the extractants of chonsurid from 1028 to 10028, for those of heparin – from 3463 to 5910, for those of ronidase – from 990 to 6236. The value of the Reynolds number changes with the use of industrial extractants and the proposed extractants with the addition of SAS for chonsurid – from 18,6 to 91,6, for heparin – from 34,8 to 265, for ronidase – from 17,5 to 65,1. The Euler number with the use of industrial extractants for chonsurid is 170, for heparin – 92,2, for ronidase – 69,9, and when using the proposed extractants with the addition of SAS, it is: 37,5; 11,3; 12, respectively. Authors assessed hydrodynamic situation on the border of the contact “solid body – liquid” using the ratio of forces of surface tension to inertial forces on the basis of dimensionless set – surface number. Surface number changes its value when using industrial extractants and the proposed extractants with the addition of SAS for chonsurid from 2295 to 2164, for heparin from 530 to 346, for ronidase from 4641 to 197. The expediency of applying surface number was proved.